Optimisation of extractive desulfurization using Choline Chloride-based deep eutectic solvents - Almashjary, Khalid Hussein; Khalid, Mohammad *; Dharaskar, Swapnil; Jagadish, Priyanka R. *; Walvekar, Rashmi; Gupta, T.C.S.M (Elsevier, 2018)
Sulfur in fuels is one of the main sources of pollution. Thus, the desulfurization of fuel (gasoline and diesel) is demanding for effective and alternative solutions. Deep eutectic solvents (DES) are gaining rapid interest in extraction processes due to their excellent properties as a solvent. In this study, extractive desulfurization (EDS) of model oil containing dibenzothiophene (DBT) as an organo-sulfur compound was carried using Choline Chloride acting as Hydrogen bond acceptor (HBA) and Propionic acid (Pr) as Hydrogen bond donor (HBD), respectively. Experiments are performed to study the effect of DES molar ratio, temperature and sonication time on DBT removal efficiency with molar ratios of 1:2 and 1:3 (HBA:HBD) using response surface methodology (RSM). DBT is quantitatively analysed using high-performance liquid chromatogram (HPLC) and Fourier transform infrared spectroscopy (FTIR) studies. The results showed high removal efficiency of 64.9% at a temperature of 37 °C, 10 min sonication; 1:3 ratio of ChCl/Pr and at a treat ratio of 1:3 model oil in a single stage extraction. This study will provide an alternative green solution which requires shorter reaction time and lower operating temperature as compared to conventional method i.e. hydrodesulfurization (HDS).